Cryptosporidium oocyst wall proteins are true components of the oocyst wall and COWP8 is not required for parasite transmission - Bacchetti, Ross; Stevens, Sarah; Lemgruber, Leandro; Gonzalez Oliva, Mariana Azevedo; Sands, Emma M.; Alexandrou, Konstantinos; Tinti, Michele; Robinson, Lee; Hanna, Jack C.; Seizova, Simona; Goddard, Peyton; Vassalli, Massimo; et al. (PLOS Pathogens, 2025)
Author summary Infection with Cryptosporidium causes diarrhoea, which can be fatal for malnourished children or people who are immunocompromised. There is no vaccine or effective medicines available to treat these patients. Infection with Cryptosporidium typically starts with drinking contaminated water that contains the parasites. Parasites are transmitted as an “oocyst” that has a hardy shell that protects parasites. This shell makes the parasites resistant to chlorination, the most common method of water disinfection. How these parasites construct this protective shell and how the shell is so resilient is unknown. When the genome of Cryptosporidium was sequenced, a group of nine proteins were predicted as shell proteins. Only one protein from this group has been studied to date. We use genetics and microscopy to confirm that the other eight proteins are involved in constructing the parasite shell. Three of these proteins appear to be specific to the seam on the shell that opens after parasites are ingested. Surprisingly, we were able to completely remove one of these genes from the genome, cowp8. Parasites that lack cowp8 are still able to construct normal shaped shells and are infectious. Using biomechanics, we find that the shells are just as strong whether they have the COWP8 protein or not. This forms a strong foundation of tools and insight to guide further investigation of the role of the shell in parasite transmission.